2021
DOI: 10.3390/ijerph18189809
|View full text |Cite
|
Sign up to set email alerts
|

Taking Up and Terminating Leisure-Time Physical Activity over the Life Course: The Role of Life Events in the Familial and Occupational Life Domains

Abstract: Leisure-time physical activity (LTPA) is associated with various health-promoting effects. However, little is known about the relationship between life events and changes in LTPA over the life course, especially when multiple life events occur simultaneously. Therefore, this study examines taking up and terminating LTPA associated with life events in the familial and occupational life domains over 16 years of 16–76-year-old Swiss inhabitants (n = 1857) in a retrospective longitudinal cohort design, using a val… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 53 publications
4
6
0
Order By: Relevance
“…This is in line with previous considerations that different life domains might compete for temporal resources as life events conflate and thus lead to a termination of leisure-time PA [ 22 ].…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…This is in line with previous considerations that different life domains might compete for temporal resources as life events conflate and thus lead to a termination of leisure-time PA [ 22 ].…”
Section: Resultssupporting
confidence: 90%
“…When it came to becoming a parent, the few mothers and one father from our study indicated that they reduced or even abandoned their sport activities, which mirrors previous research findings [ 20 , 22 ]. In this regard, Sandra pointed out how the use of her time came down to what she considered important:…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Considering this method is not the most valid with a tendency to overestimate physical activity (Ainsworth & Levy, 2004 ), efforts were made to gather the most reliable and valid data possible (e.g. reliability test, see Lenze et al., 2021 for further information). Likewise, the frequency and intensity of LTPA were not captured due to the inaccuracy of measuring them in retrospective studies (Ropponen, Levälahti, Simonen, Videman, & Battié, 2001 ); rather, the regular practice of LTPA in terms of years was captured.…”
Section: Discussionmentioning
confidence: 99%
“…LTPA is understood as physical activities including exercise, sport and unstructured recreation and excludes domestic, occupational, and commuting physical activity (Khan et al., 2012 ; see Lenze et al., 2021 for a detailed description). In this article, the term youth relates to the first 20 years of one’s life.…”
Section: Methodsmentioning
confidence: 99%